Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Faunal community ecology of central-eastern Indian Ocean Seamounts - Timothy D. O'Hara; Shane T. Ahyong; Phil Alderslade; Dianne Bray; Francesco Criscione; Niki Davey; Caroline Farrelly; Martin F. Gomon; Ana Hara; Jeremy Horowitz; Andrew M. Hosie; Lisa Kirkendale; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Pink Cricket Club: Dramatic color change in a Neotropical leaf‐masquerading katydid ( Arota festae , Griffini, 1896) - J. Benito Wainwright; Zeke W. Rowe; Matthew P. Greenwell; Patrick G. Cannon; Nathan W. Bailey; Graeme D. Ruxton (Ecology, 2026)

Genomics Reveals Extensive Population Structure and Undescribed Phylogenetic Relationships in the Cascade Torrent Salamander ( Rhyacotriton cascadae ) - Christopher D. Cousins; Deanna H. Olson; Lindsay S. Millward; Michael J. Adams; Christopher A. Pearl; Jennifer C. Rowe; Tiffany S. Garcia (Journal of Biogeography, 2026)
Aim Aims of the study are to examine patterns of range‐wide genetic differentiation and population structure in a headwater obligate salamander living in a geologically rich region, to identify genetically distinct populations and areas of gene flow between them. Location Oregon and Washington in the Pacific Northwest, United States of America. Time Period Tissue samples were collected in 2022 and 2023. Major Taxa Studied The Cascade torrent salamander Rhyacotriton cascadae . Methods Utilisation of a genome‐wide single nucleotide polymorphism (SNP) dataset from across the species range to conduct a principal components analysis (PCA), Bayesian model of population structure, co‐ancestry matrix, phylogenetic tree and estimate genetic diversity. Results There are extensive levels of population structure within R. cascadae , including a previously unknown and highly differentiated clade. Structure is characterised by an island‐like pattern wherein the species is comprised of six populations that function as independent demographic units, with gene flow largely constrained within populations. Main Conclusions Our findings reveal cryptic population structure within R. cascadae , identifying six distinct populations across the range. The northernmost population in the northwest of the species range in Washington is surprisingly highly divergent from the other five populations, and the divergence was not previously known to science. While major rivers act as phylogeographic boundaries between some populations, these boundaries appear to not always be complete.

Hemocompatibility of cyclodextrin-coated magnetic nanoparticles under uremic conditions - Mehdi Ghaffari Sharaf; Shuhui Li; Elyn M. Rowe; Noor Ali-Mohamad; Marcus Shew; Dana V. Devine; Larry D. Unsworth (Carbohydrate Polymers, 2025)

Systemic deficits in lipid homeostasis promote aging-associated impairments in B cell progenitor development - Silvia Vicenzi; Fangyuan Gao; Parker Côté; Joshua D. Hartman; Lara C. Avsharian; Ashni A. Vora; R. Grant Rowe; Hojun Li; Dorota Skowronska-Krawczyk; Leslie A. Crews (GeroScience, 2025)
Organismal aging has been associated with diverse metabolic and functional changes across tissues. Within the immune system, key features of physiological hematopoietic cell aging include increased fat deposition in the bone marrow, impaired hematopoietic stem and progenitor cell (HSPC) function, and a propensity towards myeloid differentiation. This shift in lineage bias can lead to pre-malignant bone marrow conditions such as clonal hematopoiesis of indeterminate potential (CHIP) or clonal cytopenias of undetermined significance (CCUS), frequently setting the stage for subsequent development of age-related cancers in myeloid or lymphoid lineages. Human aging has also been associated with diverse lipid alterations across tissues, such as decreased phospholipid membrane fluidity that arises as a result of increased saturated fatty acid (FA) accumulation and a decay in n-3 polyunsaturated fatty acid (PUFA) species by the age of 80 years, however the extent to which impaired FA metabolism contributes to hematopoietic aging is less clear. Here, comprehensive multi-omics analyses uncovered a role for a key PUFA biosynthesis gene, ELOVL2 , in mouse and human immune cell aging. Whole transcriptome RNA-sequencing studies and complementary flow cytometric analyses of bone marrow from aged Elovl2 mutant (enzyme-deficient) mice compared with age-matched controls revealed global downregulation in lymphoid cell markers and expression of genes involved specifically in B cell development. These studies unveiled CD79B, a vital molecular regulator of lymphoid progenitor development from the pro-B to pre-B cell stage, as a putative surface biomarker whose loss is associated with accelerated immune aging. The lipidome of mutant versus wild-type mice also displayed significant changes in the biophysical properties of cellular membranes. To investigate the relevance of these finding to human bone marrow aging, analyses of a single cell RNA-seq dataset of human HSPCs across the spectrum of human development and aging uncovered a rare subpopulation (< 7%) of CD34 + HSPCs that expresses ELOVL2 in healthy adult bone marrow. This HSPC subset, along with CD79B -expressing lymphoid-committed cells, were almost completely absent in CD34 + cells isolated from elderly bone marrow samples. Together, these findings uncover new roles for lipid metabolism enzymes in the molecular regulation of cellular aging and immune cell function in mouse and human hematopoiesis. In addition, because systemic loss of ELOVL2 enzymatic activity resulted in downregulation of B cell genes that are also associated with lymphoproliferative neoplasms, this study sheds light on an intriguing metabolic pathway that could be leveraged in future studies as a novel therapeutic modality to target blood cancers or other age-related conditions involving the B cell lineage.

Evaluation of Rock Burstability with Mechanical Property Testing and Microscopic Image Analysis - J. Malki; I. Vennes; C. D. Rowe; H. S. Mitri (Rock Mechanics and Rock Engineering, 2025)

A new approach for assessing the radioecological risk associated with the legacy discharge of oil derived natural radioactivity in the UK North Sea - F. Dal Molin; D. Hunt; A. Dewar; S. Lozach; C. Phillips; B. Thomas; L. Warford; J.E. Parker; J. Walker; M. Chocholek; D.M. Paterson; H. Woodward-Rowe; et al. (Marine Pollution Bulletin, 2025)

Brainstem Substructure Atrophy in Late-Onset GM2-Gangliosidosis Imaging Using Automated Segmentation - Olivia E. Rowe; D. Rangaprakash; Florian S. Eichler; Jeremy D. Schmahmann; Robert L. Barry; Christopher D. Stephen (The Cerebellum, 2025)

Assessment of bi-metal paleo-redox proxies in the Bakken Formation black shales, Williston Basin, North Dakota, USA - Zain Abdi; Susan M. Rimmer; Harold D. Rowe; Stephen Nordeng (Chemical Geology, 2024)

C9orf72-Associated Dipeptide Repeat Expansions Perturb ER-Golgi Vesicular Trafficking, Inducing Golgi Fragmentation and ER Stress, in ALS/FTD - Jessica Sultana; Audrey M. G. Ragagnin; Sonam Parakh; Sayanthooran Saravanabavan; Kai Ying Soo; Marta Vidal; Cyril Jones Jagaraj; Kunjie Ding; Sharlynn Wu; Sina Shadfar; Emily K. Don; Anand Deva; et al. (Molecular Neurobiology, 2024)
Hexanucleotide repeat expansions (HREs) in the chromosome 9 open reading frame 72 ( C9orf72 ) gene are the most frequent genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Both are debilitating neurodegenerative conditions affecting either motor neurons (ALS) in the brain and spinal cord or neurons in the frontal and/or temporal cortical lobes (FTD). HREs undergo repeat-associated non-ATG (RAN) translation on both sense and anti-sense strands, generating five distinct dipeptide repeat proteins (DPRs), poly-GA, -GR, -GP, -PA and -PR. Perturbed proteostasis is well-recognised in ALS pathogenesis, including processes affecting the endoplasmic reticulum (ER) and Golgi compartments. However, these mechanisms have not been well characterised for C9orf72-mediated ALS/FTD. In this study we demonstrate that C9orf72 DPRs polyGA, polyGR and polyGP (× 40 repeats) disrupt secretory protein transport from the ER to the Golgi apparatus in neuronal cells. Consistent with this finding, these DPRs also induce fragmentation of the Golgi apparatus, activate ER stress, and inhibit the formation of the omegasome, the precursor of the autophagosome that originates from ER membranes. We also demonstrate Golgi fragmentation in cells undergoing RAN translation that express polyGP. Furthermore, dysregulated ER-Golgi transport was confirmed in C9orf72 patient dermal fibroblasts. Evidence of aberrant ER-derived vesicles in spinal cord motor neurons from C9orf72 ALS patients compared to controls was also obtained. These data thus confirm that ER proteostasis and ER-Golgi transport is perturbed in C9orf72-ALS in the absence of protein over-expression. Hence this study identifies novel molecular mechanisms associated with the ER and Golgi compartments induced by the C9orf72 HRE.

Uncovering the hidden world of riverbed sediments: The role of sediment heterogeneity and cross-bar channel fills in the hydrogeochemical dynamics of the hyporheic zone - Jeffery T. McGarr; Pei Li; Robert G. Ford; Teagan Kleman; Colton Fields; Julie Hobbs; Lydia Lupton; Emma Poston; Thomas Marsh; Leah Trutschel; Ken M. Fritz; Annette Rowe; et al. (Journal of Hydrology, 2024)

Long-term effectiveness of green roofs in building sustainability through carbon emission and sequestration - Mohammad Reza Seyedabadi; Mohsen Karrabi; Jafar Nabati; D. Bradley Rowe (Environment, Development and Sustainability, 2024)

Modeling nearshore total phosphorus in Lake Michigan using linked hydrodynamic and water quality models - James J. Pauer; Mark D. Rowe; Wilson Melendez; Thomas P. Hollenhorst; Lisa L. Lowe; Peter J. Alsip; Dale M. Robertson; Steven A. Pothoven (Ecological Modelling, 2024)

Early Aboriginal pottery production and offshore island occupation on Jiigurru (Lizard Island group), Great Barrier Reef, Australia - Sean Ulm; Ian J. McNiven; Glenn R. Summerhayes; Pei-hua Wu; Magdalena M.E. Bunbury; Fiona Petchey; Quan Hua; Robert Skelly; Ariana B.J. Lambrides; Cassandra Rowe; Kelsey M. Lowe; Christian H. Reepmeyer; et al. (Quaternary Science Reviews, 2024)

Trace-metal enrichment mechanisms in Bakken Formation black shales, Williston Basin, North Dakota, USA - Zain Abdi; Susan M. Rimmer; Harold D. Rowe; Stephen Nordeng (Chemical Geology, 2024)

Utility of wastewater genomic surveillance compared to clinical surveillance to track the spread of the SARS-CoV-2 Omicron variant across England - Franziska S. Brunner; Alexander Payne; Edward Cairns; George Airey; Richard Gregory; Natalie D. Pickwell; Myles Wilson; Matthew Carlile; Nadine Holmes; Verity Hill; Harry Child; Jasmine Tomlinson; et al. (Water Research, 2023)

Adjacent and downstream effects of forest harvest on the distribution and abundance of larval headwater stream amphibians in the Oregon Coast Range - Adam Duarte; Nathan D. Chelgren; Jennifer C. Rowe; Christopher A. Pearl; Sherri L. Johnson; Michael J. Adams (Forest Ecology and Management, 2023)

Diffusion and partitioning of different PFAS compounds through thermoplastic polyurethane and three different PVC-EIA liners - R.K. Rowe; F.B. Barakat; D. Patch; K. Weber (Science of The Total Environment, 2023)

PCB containment using geosynthetics in Canada's Arctic - Daniel D. Jones; Rebecca S. McWatters; R. Kerry Rowe; Indra Kalinovich; Allison Rutter (Polar Science, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Wind and small mammals are complementary fungal dispersers - Benjamin W. Borgmann‐Winter; Ryan B. Stephens; Mark A. Anthony; Serita D. Frey; Anthony W. D'Amato; Rebecca J. Rowe (Ecology, 2023)
Following a disturbance, dispersal shapes community composition as well as ecosystem structure and function. For fungi, dispersal is often wind or mammal facilitated, but it is unclear whether these pathways are complementary or redundant in the taxa they disperse and the ecosystem functions they provide. Here, we compare the diversity and morphology of fungi dispersed by wind and three rodent species in recently harvested forests using a combination of microscopy and Illumina sequencing. We demonstrate that fungal communities dispersed by wind and small mammals differ in richness and composition. Most wind‐dispersed fungi are wood saprotrophs, litter saprotrophs, and plant pathogens, whereas fungi dispersed in mammal scat are primarily mycorrhizal, soil saprotrophs, and unspecified saprotrophs. We note substantial dispersal of truffles and agaricoid mushrooms by small mammals, and dispersal of agaricoid mushrooms, crusts, and polypores by wind. In addition, we find mammal‐dispersed spores are larger than wind‐dispersed spores. Our findings suggest that wind‐ and small‐mammal‐facilitated dispersal are complementary processes and highlight the role of small mammals in dispersing mycorrhizal fungi, particularly following disturbances such as timber harvest.

Book review - Jenna E. Bayne; Thomas Passler; Joan D. Rowe (Small Ruminant Research, 2023)

Carbon isotopic composition and organic petrography of thermally metamorphosed Antarctic coal: Implications for evaluation of δ13Corg excursions in paleo-atmospheric reconstruction - Margaret M. Sanders; Susan M. Rimmer; Harold D. Rowe (International Journal of Coal Geology, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Predicting larval alewife transport in Lake Michigan using hydrodynamic and Lagrangian particle dispersion models - Mark D. Rowe; Sara E. Prendergast; Karen M. Alofs; David B. Bunnell; Edward S. Rutherford; Eric J. Anderson (Limnology and Oceanography, 2022)
Several species of fish in large lakes and marine environments have a pelagic larval stage, and are subject to variable transport that can ultimately regulate survival and recruitment success. Alewife, Alosa pseudoharengus , are subject to transport by complex coastal currents during their pelagic larval stage (~ 30 d). We assessed backward‐trajectory simulations, consisting of a Lagrangian particle dispersion model linked to the Finite Volume Community Ocean Model, to estimate likely hatch locations of aged larval alewife collected from locations on both the eastern and western sides of Lake Michigan during July 2015. We used four deployments of three satellite‐tracked drifter buoys in coastal waters to assess model skill in estimating the origin of a drifter from its final location. We found that the trajectories of drifters varied greatly, depending on wind events and associated coastal transport processes, including upwelling/downwelling and coastal jet currents. In 2 of 12 cases, the backward trajectory simulations failed to predict the drifter origin, associated with transport of 170 km in a narrow coastal jet current. In the remaining 10 cases, the known drifter origin was within 3.5 km of the spatial patch of predicted possible origins for a scenario of horizontal diffusivity (188 m 2 s −1 ) consistent with the offshore model grid resolution. Modeled backward trajectories estimated that alewife originated from the same side of the lake where they were collected, within ~ 100 km of the collection site. Our paper demonstrates the utility of hydrodynamic models to estimate a region of origin for aged larval fish.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The use of Bayesian methodology in the development and validation of a tiered assessment approach towards prediction of rat acute oral toxicity - James W. Firman; Mark T. D. Cronin; Philip H. Rowe; Elizaveta Semenova; John E. Doe (Archives of Toxicology, 2022)
There exists consensus that the traditional means by which safety of chemicals is assessed—namely through reliance upon apical outcomes obtained following in vivo testing—is increasingly unfit for purpose. Whilst efforts in development of suitable alternatives continue, few have achieved levels of robustness required for regulatory acceptance. An array of “new approach methodologies” (NAM) for determining toxic effect, spanning in vitro and in silico spheres, have by now emerged. It has been suggested, intuitively, that combining data obtained from across these sources might serve to enhance overall confidence in derived judgment. This concept may be formalised in the “tiered assessment” approach, whereby evidence gathered through a sequential NAM testing strategy is exploited so to infer the properties of a compound of interest. Our intention has been to provide an illustration of how such a scheme might be developed and applied within a practical setting—adopting for this purpose the endpoint of rat acute oral lethality. Bayesian statistical inference is drawn upon to enable quantification of degree of confidence that a substance might ultimately belong to one of five LD50-associated toxicity categories. Informing this is evidence acquired both from existing in silico and in vitro resources, alongside a purposely-constructed random forest model and structural alert set. Results indicate that the combination of in silico methodologies provides moderately conservative estimations of hazard, conducive for application in safety assessment, and for which levels of certainty are defined. Accordingly, scope for potential extension of approach to further toxicological endpoints is demonstrated.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Lake morphometry determines Dreissena invasion dynamics - Alexander Y. Karatayev; Vadim A. Karatayev; Lyubov E. Burlakova; Knut Mehler; Mark D. Rowe; Ashley K. Elgin; Thomas F. Nalepa (Biological Invasions, 2021)

Mammals on mountainsides revisited: Trait‐based tests of assembly reveal the importance of abiotic filters - Brooks A. Kohli; Richard D. Stevens; Eric A. Rickart; Rebecca J. Rowe (Journal of Biogeography, 2021)
Aim Mountains provide uniquely informative systems for examining how biodiversity is distributed and identifying the causes of those patterns. Elevational patterns of species richness are well‐documented for many taxa but comparatively few studies have investigated patterns in multiple dimensions of biodiversity along mountainsides, which can reveal the underlying processes at play. Here, we use trait‐based diversity patterns to determine the role of abiotic filters and competition in the assembly of communities of small mammals across elevation and evaluate the surrogacy of taxonomic, functional, and phylogenetic dimensions of diversity. Location Great Basin ecoregion, western North America. Taxon Rodents and shrews. Methods The elevational distributions of 34 species were determined from comprehensive field surveys conducted in three arid, temperate mountain ranges. Elevation–diversity relationships and community assembly processes were inferred from phylogenetic (PD) and functional diversity (FD) patterns of mean pairwise and mean nearest‐neighbor distances while accounting for differences in species richness. FD indices were calculated separately for traits related to either abiotic filtering (β‐niche traits) or biotic interactions (α‐niche traits) to test explicit predictions of the role of each across elevation. Results Trait‐based tests of processes indicated that abiotic filtering tied to a strong aridity gradient drives the assembly of both low‐ and high‐elevation communities. Support for competition was not consistent with theoretical expectations under the stress‐dominance hypothesis, species interactions‐abiotic stress hypothesis, or guild assembly rule. Mid‐elevation peaks in species richness contrasted with overall FD and PD, which generally increased with elevation. PD and total FD were correlated on two of three mountains. Main conclusions The functional diversity of small mammal communities in these arid, temperate mountains is most consistent with abiotic filters, whereas support for competition is weak. Decomposing FD into traits related to separate assembly processes and examining ecoregional variation in diversity were critical for uncovering the generality of mechanisms. Divergent patterns among dimensions revealed species richness to be a poor surrogate for PD and FD across elevation and reflect the effect of biogeographic and evolutionary history. This first analysis of elevational multidimensional diversity gradients for temperate mammals provides a versatile framework for future comparative studies.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Long-term decline in the parasitism rate of passionvine hopper eggs (Scolypopa australis) - D. P. Logan; C. A. Rowe; P. G. Connolly (BioControl, 2020)

Modeling the interactive effects of nutrient loads, meteorology, and invasive mussels on suitable habitat for Bighead and Silver Carp in Lake Michigan - Peter J. Alsip; Hongyan Zhang; Mark D. Rowe; Edward Rutherford; Doran M. Mason; Catherine Riseng; Zhenming Su (Biological Invasions, 2020)
Anthropogenic stressors that affect ecological processes in the Laurentian Great Lakes can impact their susceptibility to bioinvasions. Bighead Hypophthalmichthys nobilis and Silver Carp H. molitrix , collectively ‘bigheaded carps’ (BHC), are planktivorous fishes threatening to invade Lake Michigan. While previous studies indicate the lake contains habitat suitable for BHC growth, there is a need to understand how anthropogenic-driven changes to the abiotic and biotic environment could alter its vulnerability to BHC. We applied a spatially explicit model of BHC growth rate potential (GRP; g g −1 d −1 ) to nine biophysical model scenarios to evaluate changes in habitat suitability in Lake Michigan. Scenarios differed in meteorology (cool, reference, warm), annual tributary phosphorus loads (0, 3300, and 5600 MTA), and the presence/absence of invasive dreissenid mussels. Mussel effects on BHC GRP relied on their contact with the surface mixed layer (SML), the depth of which was affected by meteorology. The warm year advanced the expansion of Bighead Carp habitat by increasing temperature-dependent foraging rates and lessening the time of competitive interaction with mussels due to earlier stratification separating mussels from the SML. Phosphorus loads were the most influential driver of the lake’s suitability. Compared to present conditions, we estimate BHC could have grown an additional 8–40% annually in the 1980s when mussels were not in the lake and phosphorus loads were higher. Our study demonstrates how climate change and nutrient enrichment can increase Lake Michigan’s vulnerability to BHC by affecting thermal regime and productivity, thereby limiting negative effects of dreissenid mussels on BHC growth.

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

Gait stability in response to platform, belt, and sensory perturbations in young and older adults - S. Roeles; P. J. Rowe; S. M. Bruijn; C. R. Childs; G. D. Tarfali; F. Steenbrink; M. Pijnappels (Medical & Biological Engineering & Computing, 2018)

Food depletion regulates the demography of invasive dreissenid mussels in a stratified lake - Alexander Y. Karatayev; Vadim A. Karatayev; Lyubov E. Burlakova; Mark D. Rowe; Knut Mehler; Mark D. Clapsadl (Limnology and Oceanography, 2018)
Lake stratification produces sharp gradients in temperature and pelagic resources which have cascading effects on the traits of aquatic populations, including invasive species and their ecosystem impacts. We study the consequences of such common environmental gradients on the demography of quagga mussels, one of the world's most aggressive invasive species. Coupling a series of in situ experiments with a biophysical model of the pelagic community, we quantify mussel growth and recruitment in littoral vs. profundal benthic habitats of eastern Lake Erie. We found that both severe food depletion and cold temperatures in the hypolimnion during summer stratification cause mussels to grow twice as slowly and currently inhibit recruitment in profundal compared to littoral habitats. Together with the high biomass and large mean mussel size found in long‐term monitoring surveys in the profundal habitats, our results imply that mussels successfully colonizing profundal habitats have relatively long lifespans with low growth rates, and therefore lower productivity, compared to mussels in shallow areas. Consequently, the bulk of dreissenid biomass in Lake Erie and other Great Lakes found in the vast but resource‐poor profundal habitats may have very limited impacts on epilimnetic communities compared to mussels in littoral areas. By contrast, mussels in profundal habitats strongly reduce food availability to hypolimnetic communities throughout the year. Thus, our results explain how the ecosystem impacts of sessile freshwater invaders are likely to vary among habitats and lakes depending on the relative size of profundal populations and the extent of stratification.

Erratum to: an analysis of failure mechanism constraints on pre-failure rock block deformation using TLS and roto-translation methods - Emily Rowe; D. Jean Hutchinson; Ryan A. Kromer (Landslides, 2018)

An analysis of failure mechanism constraints on pre-failure rock block deformation using TLS and roto-translation methods - Emily Rowe; D. Jean Hutchinson; Ryan A. Kromer (Landslides, 2018)

Influence of invasive quagga mussels, phosphorus loads, and climate on spatial and temporal patterns of productivity in Lake Michigan: A biophysical modeling study - Mark D. Rowe; Eric J. Anderson; Henry A. Vanderploeg; Steven A. Pothoven; Ashley K. Elgin; Jia Wang; Foad Yousef (Limnology and Oceanography, 2017)
We applied a three‐dimensional biophysical model to Lake Michigan for the years 2000, 2005, and 2010 to consider the mechanisms controlling spatial and temporal patterns of phytoplankton abundance (chlorophyll a ) and lake‐wide productivity. Model skill was assessed by comparison to satellite‐derived Chl a and field‐measured water quality variables. We evaluated model sensitivity to scenarios of varying mussel filter feeding intensity, tributary phosphorus loads, and warm vs. cool winter‐spring climate scenarios. During the winter‐spring phytoplankton bloom, spatial patterns of Chl a were controlled by variables that influenced surface mixed layer depth: deep mixing reduced net phytoplankton growth through light limitation and by exposing the full water column to mussel filter feeding. Onset of summer and winter stratification promoted higher surface Chl a initially by increasing mean light exposure and by separating the euphotic zone from mussels. During the summer stratified period, areas of relatively high Chl a were associated with coastal plumes influenced by tributary‐derived nutrients and coastal upwelling‐downwelling. While mussels influenced spatial and temporal distribution of Chl a , lake‐wide, annual mean primary production was more sensitive to phosphorus and warm/cool meteorology scenarios than to mussel filter feeding scenarios. Although Chl a and primary production declined over the quagga mussel invasion, our results suggest that increased nutrient loads would increase lake‐wide productivity even in the presence of mussels; however, altered spatial and temporal patterns of productivity caused by mussel filter feeding would likely persist.

Temporal shifts in the saltmarsh–Nelson’s sparrow hybrid zone revealed by replicated demographic and genetic surveys - Jennifer Walsh; W. Gregory Shriver; Maureen D. Correll; Brian J. Olsen; Chris S. Elphick; Thomas P. Hodgman; Rebecca J. Rowe; Kathleen M. O’Brien; Adrienme I. Kovach (Conservation Genetics, 2017)

Expanding the concept of sustainable seafood using Life Cycle Assessment - Friederike Ziegler; Sara Hornborg; Bridget S Green; Ole Ritzau Eigaard; Anna K Farmery; Linus Hammar; Klaas Hartmann; Sverker Molander; Robert W R Parker; Erik Skontorp Hognes; Ian Vázquez‐Rowe; Anthony D M Smith (Fish and Fisheries, 2016)
Fisheries management and sustainability assessment of fisheries more generally have recently expanded their scope from single‐species stock assessment to ecosystem‐based approaches, aiming to incorporate economic, social and local environmental impacts, while still excluding global‐scale environmental impacts. In parallel, Life Cycle Assessment ( LCA ) has emerged as a widely used and recommended framework to assess environmental impacts of products, including global‐scale impacts. For over a decade, LCA has been applied to seafood supply chains, leading to new insights into the environmental impact of seafood products. We present insights from seafood LCA research with particular focus on evaluating fisheries management, which strongly influences the environmental impact of seafood products. Further, we suggest tangible ways in which LCA could be taken up in management. By identifying trade‐offs, LCA can be a useful decision support tool and avoids problem shifting from one concern (or activity) to another. The integrated, product‐based and quantitative perspective brought by LCA could complement existing tools. One example is to follow up fuel use of fishing, as the production and combustion of fuel used dominates overall results for various types of environmental impacts of seafood products, and is also often linked to biological impacts of fishing. Reducing the fuel use of fisheries is therefore effective to reduce overall impacts. Allocating fishing rights based on environmental performance could likewise facilitate the transition to low‐impact fisheries. Taking these steps in an open dialogue between fishers, managers, industry, NGO s and consumers would enable more targeted progress towards sustainable fisheries.

Risk/Benefit Communication about Food—A Systematic Review of the Literature - L. J. Frewer; A. R. H. Fischer; M. Brennan; D. Bánáti; R. Lion; R. M. Meertens; G. Rowe; M. Siegrist; W. Verbeke; C. M. J. L. Vereijken (Critical Reviews in Food Science and Nutrition, 2016)

Magmatic–hydrothermal fluids and volatile metals in the Spirit Lake pluton and Margaret Cu–Mo porphyry system, SW Washington, USA - Alexander A. Iveson; James D. Webster; Michael C. Rowe; Owen K. Neill (Contributions to Mineralogy and Petrology, 2016)

Cities are hotspots for threatened species - Christopher D. Ives; Pia E. Lentini; Caragh G. Threlfall; Karen Ikin; Danielle F. Shanahan; Georgia E. Garrard; Sarah A. Bekessy; Richard A. Fuller; Laura Mumaw; Laura Rayner; Ross Rowe; Leonie E. Valentine; et al. (Global Ecology and Biogeography, 2016)
Aim Although urbanization impacts many species, there is little information on the patterns of occurrences of threatened species in urban relative to non‐urban areas. By assessing the extent of the distribution of threatened species across all A ustralian cities, we aim to investigate the currently under‐utilized opportunity that cities present for national biodiversity conservation. Location A ustralian mainland, T asmania and offshore islands. Methods Distributions of A ustralia's 1643 legally protected terrestrial species (hereafter ‘threatened species’) were compiled. We assessed the extent to which they overlapped with 99 cities (of more than 10,000 people), with all non‐urban areas, and with simulated ‘dummy’ cities which covered the same area and bioregion as the true cities but were non‐urban. We analysed differences between animals and plants, and examined variability within these groups using species accumulation modelling. Threatened species richness of true versus dummy cities was analysed using generalized linear mixed‐effects models. Results A ustralian cities support substantially more nationally threatened animal and plant species than all other non‐urban areas on a unit‐area basis. Thirty per cent of threatened species were found to occur in cities. Distribution patterns differed between plants and animals: individual threatened plant species were generally found in fewer cities than threatened animal species, yet plants were more likely to have a greater proportion of their distribution in urban areas than animals. Individual cities tended to contain unique suites of threatened species, especially threatened plants. The analysis of true versus dummy cities demonstrated that, even after accounting for factors such as net primary productivity and distance to the coast, cities still consistently supported a greater number of threatened species. Main conclusions This research highlights that A ustralian cities are important for the conservation of threatened species, and that the species assemblages of individual cities are relatively distinct. National conservation policy should recognize that cities play an integral role when planning for and managing threatened species.

Groundmass crystallisation and cooling rates of lava-like ignimbrites: the Grey’s Landing ignimbrite, southern Idaho, USA - B. S. Ellis; B. Cordonnier; M. C. Rowe; D. Szymanowski; O. Bachmann; G. D. M. Andrews (Bulletin of Volcanology, 2015)

Whither the megathrust? Localization of large-scale subduction slip along the contact of a mélange - John Wakabayashi; Christie D. Rowe (International Geology Review, 2015)

High influx of carbon in walls of agglutinated foraminifers during the Permian–Triassic transition in global oceans - Galina P. Nestell; Merlynd K. Nestell; Brooks B. Ellwood; Bruce R. Wardlaw; Asish R. Basu; Nilotpal Ghosh; Luu Thi Phuong Lan; Harry D. Rowe; Andrew Hunt; Jonathan H. Tomkin; Kenneth T. Ratcliffe (International Geology Review, 2015)

Comparison of stormwater runoff from sedum, native prairie, and vegetable producing green roofs - Leigh J. Whittinghill; D. Bradley Rowe; Jeffery A. Andresen; Bert M. Cregg (Urban Ecosystems, 2015)

Wave-emplaced boulders: implications for development of "prime real estate" seafront, North Coast Jamaica - S. Miller; D.-A. Rowe; L. Brown; A. Mandal (Bulletin of Engineering Geology and the Environment, 2014)

Continental‐scale assessment of genetic diversity and population structure in quaking aspen ( P opulus tremuloides ) - Colin M. Callahan; Carol A. Rowe; Ronald J. Ryel; John D. Shaw; Michael D. Madritch; Karen E. Mock (Journal of Biogeography, 2013)
Aim Quaking aspen ( P opulus tremuloides ) has the largest natural distribution of any tree native to North America. The primary objectives of this study were to characterize range‐wide genetic diversity and genetic structuring in quaking aspen, and to assess the influence of glacial history and rear‐edge dynamics. Location North America. Methods Using a sample set representing the full longitudinal and latitudinal extent of the species’ distribution, we examined geographical patterns of genetic diversity and structuring using 8 nuclear microsatellite loci in 794 individuals from 30 sampling sites. Results Two major genetic clusters were identified across the range: a south‐western cluster and a northern cluster. The south‐western cluster, which included two subclusters, was bounded approximately by the Continental Divide to the east and the southern extent of the ice sheet at the Last Glacial Maximum to the north. Subclusters were not detected in the northern cluster, despite its continent‐wide distribution. Genetic distance was significantly correlated with geographical distance in the south‐western but not the northern cluster, and allelic richness was significantly lower in south‐western sampling sites compared with northern sampling sites. Population structuring was low overall, but elevated in the south‐western cluster. Main conclusions Aspen populations in the south‐western portion of the range are consistent with expectations for a historically stable edge, with low within‐population diversity, significant geographical population structuring, and little evidence of northward expansion. Structuring within the south‐western cluster may result from distinct gene pools separated during the Pleistocene and reunited following glacial retreat, similar to patterns found in other forest tree species in the western USA . In aspen, populations in the south‐western portion of the species range are thought to be at particularly high risk of mortality with climate change. Our findings suggest that these same populations may be disproportionately valuable in terms of both evolutionary potential and conservation value.

The distribution and host range of Batrachochytrium dendrobatidis in New Zealand, 1930–2010 - Stephanie D. Shaw; Lee F. Skerratt; Amanada Haigh; Ben D. Bell; Lisa Daglish; Phillip J. Bishop; Rachel Summers; Virginia Moreno; Sabine Melzer; Michel Ohmer; Sarah Herbert; Dianne Gleeson; et al. (Ecology, 2013)
Chytridiomycosis caused by the fungal invasive pathogen Batrachochytrium dendrobatidis (Bd) was first detected in 1999 in Christchurch, New Zealand, in the Australian introduced frog species Litoria raniformis . It was detected in wild native frogs in the critically endangered Leiopelma archeyi in 2001 on the Coromandel Peninsula and has been suggested as responsible for a mass decline (88%) in that population between 1994 and 2002. We report the current distribution, host species and prevalence, where known, of Bd in New Zealand, which is essential for conservation management of New Zealand native frogs ( Leiopelma spp.). The data set is structured so that it can be readily added to the Australian Bd database for further analyses. Our data included all regions in New Zealand and six offshore islands at 135 sites with 704 records from 23 contributors spanning collection dates 1930–2010. We report 54 positive sites from 132 positive individuals. We also detail negative findings, but declaring an area free from disease should consider the sensitivity of the test used and numbers of individuals tested. The data also included a comprehensive museum survey testing 152 individuals from five species (20 L. archeyi , 50 L. hochstetteri , 15 L. aurea , 40 L. ewingii, and 27 L. raniformis ) from 1930–1999 using histology and Bd‐specific immunohistochemistry. All museum specimens were negative, so the 1999 positive result is still the earliest record. In the L. archeyi Coromandel Ranges population, the period prevalence of Bd from 2006 to 2010 was relatively stable at 16%, but the number of animals tested remains low (up to N = 19) due to the now depleted population numbers. The period prevalence of Bd in the L. archeyi Whareorino population has remained both consistent and low (6%) between 2005 and 2010. In L. hochstetteri , L. hamiltoni, and L. pakeka all sampling for Bd has been negative. Positive Bd results have been found in all three Litoria spp., but Bd has not been found in the six offshore areas tested. Most data have been previously unpublished and represent the first confirmed reports of Bd in many regions and species in New Zealand.

CCL20 Is Associated with Neurodegeneration Following Experimental Traumatic Brain Injury and Promotes Cellular Toxicity In Vitro - Christopher C. Leonardo; James Musso; Mahasweta Das; Derrick D. Rowe; Lisa A. Collier; Shyam Mohapatra; Keith R. Pennypacker (Translational Stroke Research, 2012)

The spleen contributes to stroke induced neurodegeneration through interferon gamma signaling - Hilary A. Seifert; Christopher C. Leonardo; Aaron A. Hall; Derrick D. Rowe; Lisa A. Collier; Stanley A. Benkovic; Alison E. Willing; Keith R. Pennypacker (Metabolic Brain Disease, 2012)

Quantification of total and particulate dimethylsulfoniopropionate (DMSP) in five Bermudian coral species across a depth gradient - D. M. Yost; R. Jones; C. L. Rowe; Carys Louise Mitchelmore (Coral Reefs, 2012)

Impacts of atmospheric nitrogen deposition: responses of multiple plant and soil parameters across contrasting ecosystems in long‐term field experiments - Gareth K. Phoenix; Bridget A. Emmett; Andrea J. Britton; Simon J. M. Caporn; Nancy B. Dise; Rachel Helliwell; Laurence Jones; Jonathan R. Leake; Ian D. Leith; Lucy J. Sheppard; Alwyn Sowerby; Michael G. Pilkington; et al. (Global Change Biology, 2012)
Atmospheric nitrogen ( N ) deposition is a global and increasing threat to biodiversity and ecosystem function. Much of our current understanding of N deposition impacts comes from field manipulation studies, although interpretation may need caution where simulations of N deposition (in terms of dose, application rate and N form) have limited realism. Here, we review responses to simulated N deposition from the UKREATE network, a group of nine experimental sites across the UK in a diversity of heathland, grassland, bog and dune ecosystems which include studies with a high level of realism and where many are also the longest running globally on their ecosystem type. Clear responses were seen across the sites with the greatest sensitivity shown in cover and species richness of bryophytes and lichens. Productivity was also increased at sites where N was the limiting nutrient, while flowering also showed high sensitivity, with increases and declines seen in dominant shrub and forb species, respectively. Critically, these parameters were responsive to some of the lowest additional loadings of N (7.7–10 kg ha −1 yr −1 ) showing potential for impacts by deposition rates seen in even remote and ‘unpolluted’ regions of E urope. Other parameters were less sensitive, but nevertheless showed response to higher doses. These included increases in soil % N and ‘plant available’ KCl extractable N , N cycling rates and acid–base status. Furthermore, an analysis of accumulated dose that quantified response against the total N input over time suggested that N impacts can ‘build up’ within an ecosystem such that even relatively low N deposition rates can result in ecological responses if continued for long enough. Given the responses have important implications for ecosystem structure, function, and recovery from N loading, the clear evidence for impacts at relatively low N deposition rates across a wide range of habitats is of considerable concern.

Salt tolerance of common green roof and green wall plants - Leigh J. Whittinghill; D. Bradley Rowe (Urban Ecosystems, 2011)

A Lagrangian Model to Predict the Modification of Near-Surface Scalar Mixing Ratios and Air–Water Exchange Fluxes in Offshore Flow - Mark D. Rowe; Judith A. Perlinger; Christopher W. Fairall (Boundary-Layer Meteorology, 2011)

Compositional and thermal evolution of olivine-hosted melt inclusions in small-volume basaltic eruptions: a “simple” example from Dotsero Volcano, NW Colorado - M. C. Rowe; D. W. Peate; A. Newbrough (Contributions to Mineralogy and Petrology, 2011)

Application of the probability-based Maryland Biological Stream Survey to the state’s assessment of water quality standards - Mark T. Southerland; Jon H. Vølstad; Edward D. Weber; Ronald J. Klauda; Charles A. Poukish; Matthew C. Rowe (Environmental Monitoring and Assessment, 2009)

Robust planning for restoring diadromous fish species in New Zealand's lowland rivers and streams - J.R. Leathwick; J. Elith; D. Rowe; K. Julian (New Zealand Journal of Marine and Freshwater Research, 2009)
We used statistical models to predict the distributions of 15 native diadromous fish species across New Zealand's river and stream network, and demonstrate their potential use for guiding the restoration of freshwater ecosystems. Models were fitted to an extensive collection of field samples describing the distributions of individual fish species, coupled with a set of environmental predictors chosen primarily for their functional relevance to diadromous fish species. Models were fitted to observations of species occurrence using boosted regression trees (BRT), an advanced regression technique that combines excellent predictive performance with good description of relationships between species occurrence and individual environmental predictors. Environment‐based predictions of species distributions were then made for all river and stream segments. We explored the use of these predictions to guide the selection of sites where diadromous species are likely to occur, and to set restoration targets, once a restoration site has been selected. Descriptions of the environmental preferences of the different species, based on relationships revealed by the statistical models, provide important clues to the likely responses of species to restoration of favourable environmental conditions, e.g., by restoring riparian shade and/or when reinstating access to/from the sea.

Media depth influences Sedum green roof establishment - Kristin L. Getter; D. Bradley Rowe (Urban Ecosystems, 2008)

Clonal dynamics in western North American aspen ( Populus tremuloides ) - K. E. MOCK; C. A. ROWE; M. B. HOOTEN; J. DEWOODY; V. D. HIPKINS (Molecular Ecology, 2008)
Clonality is a common phenomenon in plants, allowing genets to persist asexually for much longer periods of time than ramets. The relative frequency of sexual vs. asexual reproduction determines long‐term dominance and persistence of clonal plants at the landscape scale. One of the most familiar and valued clonal plants in North America is aspen ( Populus tremuloides ). Previous researchers have suggested that aspen in xeric landscapes of the intermountain west represent genets of great chronological age, maintained via clonal expansion in the near absence of sexual reproduction. We synthesized microsatellite data from 1371 ramets in two large sampling grids in Utah. We found a surprisingly large number of distinct genets, some covering large spatial areas, but most represented by only one to a few individual ramets at a sampling scale of 50 m. In general, multi‐ramet genets were spatially cohesive, although some genets appear to be fragmented remnants of much larger clones. We conclude that recent sexual reproduction in these landscapes is a stronger contributor to standing genetic variation at the population level than the accumulation of somatic mutations, and that even some of the spatially large clones may not be as ancient as previously supposed. Further, a striking majority of the largest genets in both study areas had three alleles at one or more loci, suggesting triploidy or aneuploidy. These genets tended to be spatially clustered but not closely related. Together, these findings substantially advance our understanding of clonal dynamics in western North American aspen, and set the stage for a broad range of future studies.

Evolution of biological dispersal corridors through a tectonically active mountain range in New Zealand - D. Craw; C. P. Burridge; P. Upton; D. L. Rowe; J. M. Waters (Journal of Biogeography, 2008)
Aim To assess the geological evolution and biogeographical implications of low mountain passes. In particular, we question the common biogeographical belief that major mountain belts form impervious physical barriers to biological dispersal, and that related taxa found on opposites sides of mountains are necessarily a result of vicariant tectonic processes. Location The Southern Alps of New Zealand form a long (500 km) narrow mountain belt at the oblique collisional Pacific–Australian tectonic plate boundary. High mountains were uplifted during the Pliocene (2–5 Ma) and uplift has continued to the present day. Methods We integrate previous work from several disciplines to obtain an overview of inter‐relationships between plate tectonic processes, geomorphology and biogeography along the main mountain barrier in New Zealand, and then extend this approach to other major mountain belts. Results The Southern Alps initially formed a barrier to at least some biological dispersal, including vicariant formation of separate species of freshwater non‐migratory galaxiid fish on either side. However, the high mountain barrier was breached in several places when passive transport of topography occurred, from the low‐erosion rain shadow on the eastern side towards the high‐erosion, high‐rainfall western side. This tectonic transport resulted in the capture of eastern rivers by west‐draining rivers, leaving low passes at the topographic divide. These low‐elevation corridors permitted biological dispersal across the mountains, although continued uplift raises these passes. A new set of passes has formed in the northern part of the mountains where younger faults are cutting across the older mountain topography. These potential dispersal corridors are becoming lower with continued erosion, and more common as the defining structures migrate southwards. Main conclusions Biological dispersal across the Southern Alps may be facilitated by numerous mountain passes, especially via the new passes formed by cross‐cutting faults. More low‐lying corridors existed than is readily apparent now, as old river capture‐related passes have been blocked by ongoing uplift. The dynamic mountain‐building and erosional environment typified by the Southern Alps occurs in all the world’s collisional mountain belts, such as the Andes, Himalayas, European Alps and North American Cordillera. Sister taxa occurring across mountain belts are not necessarily a result of vicariance driven by the rise of the mountains, as numerous passes may have permitted intermittent dispersal. The evolution of low passes may have been more prevalent than is currently appreciated, suggesting that topographically complex mountain ranges might be more effectively viewed as dynamic filters within a probability landscape rather than as static and impervious high‐altitude barriers to all but the rarest of biological dispersal events. In some cases, the biological disjunctions observed across mountains may more directly reflect habitat differentiation driven by orographic mountain development that has limited the probability of trans‐alpine dispersal success.

Dispersal, disturbance and the contrasting biogeographies of New Zealand’s diadromous and non‐diadromous fish species - J. R. Leathwick; J. Elith; W. L. Chadderton; D. Rowe; T. Hastie (Journal of Biogeography, 2008)
Aim To examine the relationship between diadromy and dispersal ability in New Zealand’s freshwater fish fauna, and how this affects the current environmental and geographic distributions of both diadromous and non‐diadromous species. Location New Zealand. Methods Capture data for 15 diadromous and 15 non‐diadromous fish species from 13,369 sites throughout New Zealand were analysed to establish features of their geographic ranges. Statistical models were used to determine the main environmental correlates of species’ distributions, and to establish the environmental conditions preferred by each species. Environmental predictors, chosen for their functional relevance, were derived from an extensive GIS database describing New Zealand’s river and stream network. Results In terms of geography, most diadromous species occur in a scattered fashion throughout extensive geographic ranges, and occupy large numbers of catchments of widely varying size. By contrast, most non‐diadromous species show relatively high levels of occupancy of smaller geographic ranges, and most are restricted to a few large catchments, particularly in the eastern South Island. In terms of environment, there is marked separation of diadromous from non‐diadromous species, with diadromous species generally caught most frequently in low‐gradient coastal rivers and streams with warm, maritime climates. With a few notable exceptions, most diadromous species have lower occurrence in river segments that are located above obstacles to upstream migration. Non‐diadromous species are usually caught in inland rivers and streams with cool, strongly seasonal climates, typified by a low frequency of high‐intensity rainfall events. Main conclusions We interpret the contrasting biogeographies of New Zealand’s diadromous and non‐diadromous species as reflecting interaction between their marked differences in dispersal ability and a landscape that is subject to recurrent, often large‐scale, natural disturbance. While both groups are likely to be equally susceptible to local, disturbance‐driven extinction, the much greater dispersal ability of diadromous species has allowed them to persist over wide geographic ranges. By contrast, the distributions of most non‐diadromous species are concentrated in a few large catchments, mostly in regions where less intense natural disturbance regimes are likely to have favoured their survival.

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Life at low temperatures: A novel breeding‐system adjustment in a polar cladoceran - Paul D. N. Hebert; Chad L. Rowe; Sarah J. Adamowicz (Limnology and Oceanography, 2007)
The typical breeding system of cladocerans, cyclic parthenogenesis, is poorly suited to polar settings because it requires one or more rounds of parthenogenesis before the production of males and sexual eggs. Past work has shown that many arctic cladocerans have secondarily made the transition to obligate, apomictic parthenogenesis. Arctic populations of Holopedium gibberum lack males, suggesting their possible adoption of this breeding system. However, this study shows that these lineages instead possess genotypic characteristics expected under either self‐fertilization or automictic parthenogenesis, the first record of such a breeding system in the Cladocera. As populations of Holopedium from southerly areas reproduce by cyclic parthenogenesis, this breeding system transition appears to represent an adaptive response to living at low temperatures.

Microbial communities and geochemical dynamics in an extremely acidic, metal‐rich stream at an abandoned sulfide mine (Huelva, Spain) underpinned by two functional primary production systems - Owen F. Rowe; Javier Sánchez‐España; Kevin B. Hallberg; D. Barrie Johnson (Environmental Microbiology, 2007)
Summary An extremely acidic (pH 2.5–2.75) metal‐rich stream draining an abandoned mine in the Iberian Pyrite Belt, Spain, was ramified with stratified macroscopic gelatinous microbial growths (‘acid streamers’ or ‘mats’). Microbial communities of streamer/mat growths sampled at different depths, as well as those present in the stream water itself, were analysed using a combined biomolecular and cultivation‐based approach. The oxygen‐depleted mine water was dominated by the chemolithotrophic facultative anaerobe Acidithiobacillus ferrooxidans , while the streamer communities were found to be highly heterogeneous and very different to superficially similar growths reported in other extremely acidic environments. Microalgae accounted for a significant proportion of surface streamer biomass, while subsurface layers were dominated by heterotrophic acidophilic bacteria ( Acidobacteriacae and Acidiphilium spp.). Sulfidogenic bacteria were isolated from the lowest depth streamer growths, where there was also evidence for selective biomineralization of copper sulfide. Archaeal clones (exclusively Euryarchaeota ) were recovered from streamer samples, as well as the mine stream water. Both sunlight and reduced inorganic chemicals (predominantly ferrous iron) served as energy sources for primary producers in this ecosystem, promoting complex microbial interactions involving transfer of electron donors and acceptors and of organic carbon, between microorganisms in the stream water and the gelatinous streamer growths. Microbial transformations were shown to impact the biogeochemical cycling of iron and sulfur in the acidic stream, severely restricting the net oxidation of ferrous iron even when the initially anoxic waters were oxygenated by indigenous acidophilic algae. A model accounting for the biogeochemistry of iron and sulfur in the mine waters is described, and the significance of the acidophilic communities in regulating the geochemistry of acidic, metal‐rich waters is described.

Vegetation Type Affects the Relationship Between Soil Carbon to Nitrogen Ratio and Nitrogen Leaching - E. C. Rowe; C. D. Evans; B. A. Emmett; B. Reynolds; R. C. Helliwell; M. C. Coull; C. J. Curtis (Water, Air, & Soil Pollution, 2006)

Stable isotopic fingerprint of a hyporheic–hypolentic boundary in a reservoir - Todd A. Aseltyne; Harold D. Rowe; Alan E. Fryar (Hydrogeology Journal, 2006)

Hydrologic-energy balance constraints on the Holocene lake-level history of lake Titicaca, South America - H. D. Rowe; R. B. Dunbar (Climate Dynamics, 2004)

Genetic variability and heritability estimates for hardseededness and flowering in balansa clover (Trifolium michelianum Savi) populations - Ramakrishnan M. Nair; Andy D. Craig; Trevor D. Rowe; Steve R. Biggins; Colleen H. Hunt (Euphytica, 2004)

Seasonal profiles in growth, energy reserves, gonad development, and plasma steroids in age 1+ cultured Chinook salmon (Oncorhynchus tshawytscha) females - M. J. Unwin; C. W. Poortenaar; D. K. Rowe; N. C. Boustead; M. J. R. Porter (New Zealand Journal of Marine and Freshwater Research, 2004)
Sexual maturation in 2‐year‐old female Chinook salmon (Oncorhynchus tshawytscha) is unknown within their native range, but occurs in up to 20% of farmed stocks in New Zealand. To characterise the seasonal timing of oogenesis and subsequent ovarian development, we measured levels of plasma 17β‐estradiol and testosterone, condition factor, and gonadosomatic and hepatosomatic index, for freshwater‐reared female Chinook at 2–4‐week intervals during their second year of life (May 2001‐April 2002). These comprised two treatment groups under additional 24 h illumination from September to January, and two ambient controls. Macroscopic ovarian development first occurred in mid September (8 months before spawning), coinciding with detectable increases (≥0.3 ng ml ‐1 ) in both plasma steroids. Vitellogenesis was first observed in November and coincided with an increase in hepatosomatic index, possibly indicating the liver's role in transferring lipids to the developing ova. Neither mean weight nor the percentage of maturating fish (mean 6.9%) differed between the treatment and control groups at the end of the experiment, but ovarian development in the treatment group was advanced by 13 days relative to the controls. Reduced dark phase plasma melatonin levels confirmed that the additional light was sufficiently intense to produce a physiological response in the artificially illuminated fish.

Conserved simple sequence repeats for the Limnanthaceae (Brassicales) - V. K. Kishore; P. Velasco; D. K. Shintani; J. Rowe; C. Rosato; N. Adair; M. B. Slabaugh; S. J. Knapp (Theoretical and Applied Genetics, 2004)

Chemical Contaminants and their Effects in Fish and Wildlife from the Industrial Zone of Sumgayit, Republic of Azerbaijan - Carol D. Swartz; K.C. Donnelly; Arif Islamzadeh; Gilbert T. Rowe; William J. Rogers; Grigoriy M. Palatnikov; Arif A. Mekhtiev; Rafik Kasimov; Thomas J. McDonald; Jeffery K. Wickliffe; Bobby J. Presley; John W. Bickham (Ecotoxicology, 2003)

Editorial: The Unknown Environmental Tragedy in Sumgayit, Azerbaijan - John W. Bickham; Cole W. Matson; Arif Islamzadeh; Gilbert T. Rowe; K.C. Donnelly; Carol D. Swartz; William J. Rogers; Jeffrey K. Wickliffe; Robin L. Autenrieth; Thomas J. McDonald; Dmitri Politov; Grigoriy Palatnikov; et al. (Ecotoxicology, 2003)

Increased Efficiency of Transgenic Livestock Production - Elizabeth A. Maga; R. Geoffrey Sargent; Hong Zeng; Sushma Pati; David A. Zarling; Stefanie M. Oppenheim; Nicole M.B. Collette; Alice L. Moyer; Janice S. Conrad-Brink; Joan D. Rowe; Robert H. BonDurant; Gary B. Anderson; et al. (Transgenic Research, 2003)

Ecotoxicological Implications of Aquatic Disposal of Coal Combustion Residues In the United States: A Review - Christopher L. Rowe; William A. Hopkins; Justin D. Congdon (Environmental Monitoring and Assessment, 2002)

Phylogenetic relationships of dengue-1 viruses from Argentina and Paraguay - G. Avilés; J. Rowe; J. Meissner; J. C. Manzur Caffarena; D. Enria; S. St. Jeor (Archives of Virology, 2002)

Use of GIS to predict effects of water level on the spawning area for smelt, Retropinna retropinna , in Lake Taupo, New Zealand - D. K. ROWE; U. SHANKAR; M. JAMES; B. WAUGH (Fisheries Management and Ecology, 2002)
A GIS model of the littoral bathymetry and substrate composition of Lake Taupo was created using ArcInfo. Littoral substrates were mapped by aerial photography and confirmed by ground‐truthing. Water depths were determined by echosounding linked to a differential GPS. These data were imported into ArcInfo where a 3D GIS model was used to calculate the total area of smelt, Retropinna retropinna Richardson, spawning habitat (i.e. clean sand between depths of 0.5–2.5 m) at each of five lake levels. There was little change in area over the first 50 cm below the natural maximum lake level, but spawning habitat decreased rapidly over the next 1.4 m such that a 30% reduction occurred at the natural minimum level. Anecdotal information on inter‐annual variations in lake level and smelt abundance supported the notion that high lake levels in spring result in high recruitment of smelt. The GIS model also predicted effects of lake level change on areas of macrophyte cover and on other littoral substrates, and could be used to assess effects of lake level changes on the habitats of other biota.

Nitrogen nutrition of hedged stock plants of Loblolly Pine. II. Influence of carbohydrate and nitrogen status on adventitious rooting of stem cuttings - D. Bradley Rowe; Frank A. Blazich; Barry Goldfarb; Farrell C. Wise (New Forests, 2002)

Nitrogen nutrition of hedged stock plants of Loblolly Pine. I. Tissue nitrogen concentrations and carbohydrate status - D. Bradley Rowe; Frank A. Blazich; C. David Raper (New Forests, 2002)

Insolation, Moisture Balance and Climate Change on the South American Altiplano Since the Last Glacial Maximum - Harold D. Rowe; Robert B. Dunbar; David A. Mucciarone; Geoffrey O. Seltzer; Paul A. Baker; Sherilyn Fritz (Climatic Change, 2002)

Accumulation and Selective Maternal Transfer of Contaminants in the Turtle Trachemys scripta Associated with Coal Ash Deposition - R. D. Nagle, C. L. Rowe, J. D. Congdon (Archives of Environmental Contamination and Toxicology, 2001)

Recovery ofVerticillium dahliae from North American certified seed potatoes and characterization of strains by vegetative compatibility and aggressiveness - M. A. Omer; D. A. Johnson; R. C. Rowe (American Journal of Potato Research, 2000)

Considerations on the use of video playbacks as visual stimuli: the Lisbon workshop consensus - R. F. Oliveira; G. G. Rosenthal; I. Schlupp; P. K. McGregor; I. C. Cuthill; J. A. Endler; L. J. Fleishman; J. Zeil; E. Barata; F. Burford; D. Gonçalves; M. Haley; et al. (acta ethologica, 2000)

Factors influencing the abundance of the common bully, Gobiomorphus cotidianus McDowall, in small, North Island, New Zealand, lakes - D. K. Rowe (Fisheries Management and Ecology, 1999)
Adult common bullies, Gobiomorphus cotidianus McDowall, are small (total length = 30–120 mm), benthic fish commonly found in the littoral zones of New Zealand lakes where they are a major prey species for trout and eels. Differences in their relative abundance (CPUE) were determined between 21 shallow North Island lakes. Mean CPUE ranged from 2 to > 1000 fish net − 1 night − 1 and was inversely related to water transparency. The abundance of bullies was not reduced in lakes containing rainbow trout, Oncorhynchus mykiss (Walbaum), but was reduced in all lakes containing self‐recruiting populations of eels, Anguilla spp. Mean densities of planktonic larval bullies in the limnetic zone were also inversely related to water transparency. Since low water transparency is related to increased trophic status for these lakes, the abundance of bullies is likely to be related to lake productivity, rather than turbidity.

The response of trout and zebrafish embryos to low and high boron concentrations is U-shaped - Ruby I. Rowe; Collen Bouzan; Sam Nabili; Curtis D. Eckhert (Biological Trace Element Research, 1998)

Acute and Genotoxic Effects of Baku Harbor Sediment on Russian Sturgeon, Acipenser guildensteidti - J. W. Bickham; G. T. Rowe; G. Palatnikov; A. Mekhtiev; M. Mekhtiev; R. Y. Kasimov; D. W. Hauschultz; J. K. Wickliffe; W. J. Rogers (Bulletin of Environmental Contamination and Toxicology, 1998)

Elevated Trace Element Concentrations in Southern Toads, Bufo terrestris, Exposed to Coal Combustion Waste - W. A. Hopkins; M. T. Mendonça; C. L. Rowe; J. D. Congdon (Archives of Environmental Contamination and Toxicology, 1998)

Enhanced hydrogen peroxide sensitivity and altered stress protein expression in iron-starved Mycobacterium smegmatis - Michael D. Lundrigan; Jean E.L. Arceneaux; Wenming Zhu; B. Rowe Byers (BioMetals, 1997)

Resistance exercise training and the orthostatic response - John P. McCarthy; Marcas M. Bamman; Janice M. Yelle; Adrian D. LeBlanc; Roger M. Rowe; Michael C. Greenisen; Stuart M. C. Lee; Elisabeth R. Spector; Suzanne M. Fortney (European Journal of Applied Physiology, 1997)

Further analysis of the role of spectrin repeat motifs in α-actinin dimer formation - G. Flood; A. J. Rowe; D. R. Critchley; W. B. Gratzer (European Biophysics Journal, 1997)

Migration between nests in the Australian arid‐zone ant Rhytidoponera sp. 12 revealed by DGGE analyses of mitochondrial DNA - W. Tek Tay; J. M. Cook; D. J. Rowe; R. H. Crozier (Molecular Ecology, 1997)
Denaturing gradient gel electrophoresis (DGGE) of a PCR‐amplified region of the mitochondrial DNA (mtDNA) including a large part of the cytochrome b gene revealed four haplotypes among worker ants from 75 colonies of the queenless ant Rhytidoponera sp. 12. The DGGE results were checked by sequencing examples of the haplotypes; all changes were transitions and two haplotypes differed by only a single substitution. Previous work (e.g. Crozier et al. 1984) showed that intranest relatedness is low for nuclear genes yet neighbouring nests are related; gene flow via winged males appeared the best explanation for this phenomenon. Two mtDNA haplotypes were found in 34.7% of the colonies studied, showing that female movement also occurs between nests. Migration of mated individuals on such a large scale when the number of reproductives is relatively small is unexpected (Crozier & Pamilo 1996). An observed tendency to clumping of the haplotypes is in accordance with the wingless nature of the female dispersers.

An intact peripheral nerve preparation for monitoring inputs from single muscle afferent fibres - P. D. Mackie; M. J. Rowe (Experimental Brain Research, 1997)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

The accumulation and loss of dieldrin and endrin in the Eastern oyster - J. W. Mason; D. R. Rowe (Archives of Environmental Contamination and Toxicology, 1976)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)

Editorial - E. Norrby; W. P. Rowe; C. Scholtissek; D. A. J. Tyrrell; J. Vilček (Archives of Virology, 1975)

Die Erkrankung der Maus durch das Virus der Stomatitis vesicularis - D. Falke; W. P. Rowe (Archives of Virology, 1965)

Die Erkrankung der Maus durch das Virus der Stomatitis vesicularis - D. Falke; W. P. Rowe (Archives of Virology, 1965)

Die Interferenz zwischen dem Polyoma-Virus und dem Stomatitis-vesicularis-Virus in der Maus - D. Falke; W. P. Rowe (Archives of Virology, 1965)